Chronic or atrophie masticatory myositis in the dog. A report of two spontaneous cases - KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F.; VAMVAKIDIS (Χ. Δ. ΒΑΜΒΑΚΙΔΗΣ) C. D.; POLIZOPOULOU (Ζ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z.; LEKKAS (Σ. ΛΕΚΚΑΣ) S.; GEORGIADIS (Γ. ΓΕΩΡΓΙΑΔΗΣ) G. (Journal of the Hellenic Veterinary Medical Society, 2018)
Two young adult dogs (case 1: German wirehaired pointer male, case 2: mongrel female) were admitted to our Clinic because of a progressive, bilateral and symmetrical atrophy of the masticatory muscles, that was most obvious in the temporal muscles. No signs of mandibular dysfunction were detected in both animals. The clinical diagnosis of chronic or atrophic myositis was confirmed by the histopathology of temporal muscle biopsies, which revealed the typical of the disease lesions, such as myofiber degeneration, regeneration and atrophy, interstitial or perivascular cellular infiltrates, chiefly of lymphocytes and plasma cells plus perimysial fibrosis. Temporal muscle electromyography, done only in case 1, showed abnormal spontaneous activity indicating myositis. The use of prednisolone at immunosuppressive doses, with or without azathioprine, not only stopped the progression of the disease but resulted in a partial restoration of the masticatory muscle mass.